Highly water-reducing powder preparation for dry mortar

By adjusting the structural unit ratio and spray drying conditions of PCE type copolymer, the powdered copolymer P with optimized particle size distribution and low agglomeration tendency was prepared, and the performance of powdered PCE type copolymer in the dry mortar in the prior art was solved. The problem of insufficient results has achieved better fluidity, slump life and pressure resistance.

CN111747671BActive Publication Date: 2025-02-18SIKA TECH AG
View PDF 13 Cites 0 Cited by

Patent Information

Application Number
CN201910229736.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2019-03-26
Publication Date
2025-02-18
Estimated Expiration
2039-03-26

Smart Images

  • Figure CN111747671B_ABST
    Figure CN111747671B_ABST
Patent Text Reader

Abstract

The present invention relates to PCE type copolymers in powder form, which can be obtained by spray drying and are easily redispersible in water. The fineness and anti-caking properties of said PCE type copolymers in powder form, as well as their water reduction potential and influence on the slump life are improved. The present invention also relates to a process for producing said PCE type copolymers in powder form by a spray drying process, and their use for improving mineral binder compositions and in particular dry mortars.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to PCE-type copolymers in powder form which can be redispersed in water, to the production of said PCE-type copolymers in powder form and to the use of such powdered PCE-type copolymers for modifying dry mortars. Background of the Invention

[0002] Copolymers of polycarboxylates / salts and polyalkylene glycols (PCEs) have been known for many years to be used as dispersing aids for aqueous dispersions, in particular for aqueous dispersions of mineral binders. PCEs act as superplasticizers and reduce the water required to achieve a certain level of fluidity for a given uncured mineral binder composition. Reduction of water in mineral binder compositions, in particular cementitious compositions, is desirable because it results in less separation of solid components in the uncured composition and increased compressive strength of the cured composition.

[0003] Pre-batched dry mortars are now being used in new construction and renovation work. The advantage of such dry mortars over mortars batched on the construction site is improved consistency of properties, such as flowability, setting kinetics and final strength. The use of PCE in dry mortars requires a dry consistency, preferably said PCE in powdered form. Furthermore, the dry consistency of PCE reduces the transportation and storage costs of said PCE, especially if the dry PCE can be redispersed in water and thus an aqueous solution or dispersion can be easily prepared at the point of use.

[0004] WO2006 / 133933 discloses PCE type copolymers of ethylenically unsaturated monocarboxylic acid based monomers copolymerized with monomers based on unsaturated long chain polyalkylene glycol ethers. The copolymers can be spray dried to form powders. However, the architecture of the disclosed copolymers is not optimal for the spray drying process. Thus, powders are produced which have a tendency to agglomerate and a particle size distribution which is not optimal for use in drying mortars.

[0005] WO2006 / 129883 discloses a PCE type copolymer with a degree of neutralization <50% which results in improved pulverization properties. Pulverization can be carried out by different means, including spray drying methods. One disadvantage is that due to the low degree of neutralization there is still an increased tendency for the powder to agglomerate.

[0006] WO00 / 47533 discloses a powdered PCE-based polymer composition containing a mineral carrier, including silica. These powders are reported to have improved powder flowability and improved anti-caking properties compared to powders of the same PCE-type copolymers from a spray drying process. One disadvantage of these powders is that they cannot be easily redispersed to prepare stable aqueous polymer dispersions again.

[0007] CN101824125 discloses a PCE type copolymer having a polyalkylene glycol chain with a molecular weight of 600-2000 g / mol. A spray drying method for obtaining a powdered product is also disclosed. However, the disclosed spray drying method operates at high temperature, which requires higher energy input and carries the risk of degradation of the PCE type copolymer during the spray drying process.

[0008] CN101962273 discloses a method for preparing powdered PCE type copolymers, which incorporates inorganic particles in a spray drying process. However, a large amount of mineral carrier needs to be added to the spray drying process to produce acceptable powder quality. In addition, the disclosed spray drying process operates at high temperatures, which requires higher energy input and carries the risk of PCE type copolymer degradation during the spray drying process.

[0009] Finally, US7030178 discloses a powdered dispersant for hydraulically setting compositions based on a PCE-type copolymer whose degree of alkoxylation in the side chains is 45-150, whose ratio of monomers with alkoxylated side chains is 15-45 mol % and whose degree of neutralization of carboxyl groups is 70-80%. Spray drying is mentioned as a method for obtaining said powdered dispersant. A disadvantage is that, due to the disclosed degree of neutralization, there is still a pronounced tendency for the powder to agglomerate.

[0010] There is therefore a need for powdered PCE compositions that can be easily prepared by spray drying and that overcome the above-mentioned disadvantages. Summary of the invention

[0011] An object of the present invention is to provide a powdered PCE type copolymer which can be obtained by spray drying. In particular, the fineness and anti-caking properties of the powder, as well as the water reduction potential and the influence on the slump life of the powdered PCE type copolymer in a mineral binder composition should be improved with respect to the prior art.

[0012] Another object of the present invention is to provide a spray drying method for producing the powdered PCE type copolymer.

[0013] Another object of the present invention is to provide a method and use of the powdered PCE type copolymers described for improving mineral binder compositions and in particular dry mortars.

[0014] Surprisingly it has been found that the object of the present invention can be achieved according to claim 1 by a powdered copolymer P comprising at least 80 w %, preferably at least 85 w %, more preferably at least 90 w %, each based on the total weight of the powder, of a PCE-type copolymer comprising:

[0015] a) a molar parts of structural unit S1 of formula I

[0016]

[0017] b) b molar parts of structural unit S2 of formula II

[0018]

[0019] c) c molar parts of structural unit S3 of formula III

[0020]

[0021] d) d molar parts of structural unit S4 of formula IV

[0022]

[0023] in

[0024] Each M represents H independently of each other + , alkali metal ions, alkaline earth metal ions, divalent or trivalent metal ions, ammonium ions or organic ammonium groups,

[0025] Each R u independently of one another represent hydrogen or methyl,

[0026] Each R v independently of each other represent hydrogen or COOM,

[0027] m = 0, 1, 2 or 3,

[0028] p = 0 or 1,

[0029] Each R 1 and each R 2 Independently represent C1- to C 20 -alkyl, -cycloalkyl, -alkylaryl or -[AO] n -R 4 ,

[0030] Where A = C2- to C4-alkylene, R 4 Indicates H, C1- to C 20 -alkyl, -cyclohexyl or -alkylaryl,

[0031] and n = 2-350,

[0032] Each R 3 Independent of other representations NH2, -NR 5 R 6 , -OR 7 NR 8 R 9 ,

[0033] Where R 5 and R 6 Independently express

[0034] C1- to C 20 -alkyl, -cycloalkyl

[0035] -alkylaryl or -aryl,

[0036] or represents a hydroxyalkyl- or acetoxyethyl-(CH3-CO-O-CH2-CH2-) or a hydroxyisopropyl-(HO-CH(CH3)-CH2-) or an acetoxyisopropyl (CH3-CO-O-CH(CH3)-CH2-);

[0037] or R 5 and R 6 together to form a ring of which the nitrogen is a part, thereby forming a morpholine or imidazoline ring,

[0038] R 7 is a C2-C4-alkylene group,

[0039] Each R 8 and R 9 Independently represent C1- to C 20 -alkyl, -cycloalkyl, -alkylaryl,

[0040] - aryl or hydroxyalkyl,

[0041] and wherein a, b, c and d represent the molar fractions of the structural units S1, S2, S3 and S4, and

[0042] a / b / c / d / =(0.1–0.9) / (0.05–0.9) / (0.0–0.8) / (0.0–0.8),

[0043] The premise is a+b+c+d=1, and

[0044] Characterized in that the particle size distribution of the powdered copolymer P is D90 value <250 μm, preferably <225 μm, in particular <210 μm, D10 value <60 μm, preferably <50 μm, in particular <40 μm, and D50 value is 70-130 μm, preferably 75-120 μm, in particular 80-100 μm.

[0045] It has been found that the powdered copolymers P described above can advantageously be used in dry mortar formulations to reduce the water requirement for the dry mortar and / or to increase the fluidity of compositions based on said dry mortar.

[0046] A further advantage of the powdered copolymers P according to the invention is that the mineral binder compositions comprising said powdered copolymers P have less separation after mixing with the mixing water.

[0047] Yet another advantage of the present invention is that the powdered copolymer P results in a mineral binder composition having an improved slump life after mixing with water compared to the same mineral binder composition without the powdered copolymer P but comprising a prior art PCE type copolymer. Improved slump life means that after a certain period of time after mixing the mineral binder composition with water, the change in slump flow is minimized.

[0048] Finally, one advantage of the powdered copolymers P of the invention is that the compressive strength of the cured mineral binder compositions comprising said powdered copolymers P, in particular when measured 1 day or 3 days after mixing with water, is increased compared to mineral binder compositions having the same fluidity level but comprising PCE type copolymers of the prior art.

[0049] Further aspects of the invention are the subject matter of further independent claims. Particularly preferred embodiments of the invention are the subject matter of the dependent claims.

[0050] Mode for carrying out the invention

[0051] The expression "mineral binder" in the context of the present invention refers in particular to a binder which reacts in the presence of water in a hydration reaction to form a solid hydrate or a hydrate phase. This can be, for example, a hydraulic binder (for example cement or hydraulic lime), a latent hydraulic binder (for example slag), a pozzolanic binder (for example fly ash) or a non-hydraulic binder (gypsum plaster or white lime). A "mineral binder composition" is therefore a composition containing at least one mineral binder.

[0052] According to an embodiment, the mineral binder or the mineral binder composition comprises a hydraulic binder, preferably cement. Particularly preferred is a cement with a cement clinker content of ≥ 35% by weight. In particular, the cement is of type CEM I, II, III (according to standard EN 197-1) or calcium aluminate cement (according to standard EN 14647: 2006-01) or calcium sulphoaluminate cement or a mixture thereof. The proportion of hydraulic binder in the total mineral binder is advantageously at least 5% by weight, in particular at least 20% by weight, preferably at least 35% by weight, in particular at least 65% by weight. In another advantageous embodiment, the mineral binder consists to an extent of at least 95% by weight of hydraulic binder, in particular cement clinker.

[0053] In an advantageous embodiment, the cement further comprises up to 40w%, preferably up to 35w%, in particular up to 20w% of calcium sulfate, each based on the total dry weight of the cement. The calcium sulfate may be present in the form of calcium sulfate hemihydrate, calcium sulfate dihydrate and / or anhydrite.

[0054] According to another embodiment, the binder composition comprises other binders in addition to the hydraulic binder or instead of the hydraulic binder. They are especially latent hydraulic binders and / or pozzolanic binders. Suitable latent hydraulic and / or pozzolanic binders are, for example, slag, fly ash and / or silica dust. In an advantageous embodiment, the mineral binder comprises 5-95% by weight, in particular 5-65% by weight, in particular 15-35% by weight of latent hydraulic and / or pozzolanic binders.

[0055] As used in the context of the present invention, the term "aggregate" refers to a mineral material that is non-reactive in the hydration reaction of a mineral binder. The aggregate may be any aggregate commonly used in cementitious materials such as concrete, mortar, screed, render, slurry, paint, putty, etc. Typical aggregates are, for example, rock, crushed stone, gravel, slag, limestone, sand, recycled concrete, perlite or vermiculite.

[0056] "Dry mortar" in the context of the present invention refers to a composition containing at least one of the above-mentioned mineral binders and typically aggregates and additives selected from the following: plasticizers, superplasticizers, rheology modifiers, retarders, air entraining agents, deaerators, corrosion inhibitors, fibers, synthetic organic polymers, expansion-generating additives, pigments, strength enhancers, waterproofing additives, alkali-aggregate reaction inhibitors, chromate reducers and / or biocides. Dry mortar may contain a small amount of water. Dry mortar has a solid consistency, in particular a powdered consistency. Dry mortar is typically pre-batched in the factory and delivered to the construction site. Dry mortar can be formulated for use as a repair mortar for concrete, as a leveling material, a render, a coating, a putty, a mud or a water plugging agent, and for waterproofing or fireproofing applications.

[0057] "Particle size distribution" in the context of the present invention is a list of values ​​that define the relative amount of particles present according to size. The particle size distribution can be described by different D-values. For example, the D10 value is the particle diameter at which 10% of the particles of a given distribution are smaller than this diameter and 90% of the particles of a given distribution are larger than this diameter. Similarly, the D90 value is the diameter at which 90% of a given sample contains particles with a diameter smaller than this value. Unless otherwise indicated, the term "particle size" refers in the present invention to the median value of the particle size distribution of a solid. This median value is given as the D50 value for a given particle size distribution and constitutes the value of the particle diameter at 50% in the cumulative distribution. The D50 value is usually interpreted as the particle size at which 50% of the particles of a given distribution are larger than this particle size and 50% are smaller than this particle size. D50 is therefore the median.

[0058] The particle size distribution and thus the various D values ​​and the particle sizes defined above can be determined in particular by laser scattering, preferably in accordance with standard ISO 13320: 2009. In particular, the Mastersizer 2000 instrument with Hydro 2000G dispersion unit and Mastersizer 2000 software from Malvern Instruments GmbH (Germany) can be used for this purpose.

[0059] The term "slump life" in the context of the present invention relates to the time after mixing a mineral binder composition with water until the slump starts to decrease, as measured for example by ASTM C 143. Generally, a longer slump life is advantageous, since the mineral binder composition will thereby be workable for longer.

[0060] The powdered copolymer P of the present invention comprises at least 80 w%, preferably at least 85 w%, more preferably at least 90 w%, each based on the total weight of the powder, of a PCE type copolymer comprising:

[0061] a) a molar parts of structural unit S1 of formula I

[0062]

[0063] b) b molar parts of structural unit S2 of formula II

[0064]

[0065] c) c molar parts of structural unit S3 of formula III

[0066]

[0067] d) d molar parts of structural unit S4 of formula IV

[0068]

[0069] in

[0070] Each M represents H independently of each other + , alkali metal ions, alkaline earth metal ions, divalent or trivalent metal ions, ammonium ions or organic ammonium groups,

[0071] Each R u independently of one another represent hydrogen or methyl,

[0072] Each R v independently of each other represent hydrogen or COOM,

[0073] m = 0, 1, 2 or 3,

[0074] p = 0 or 1,

[0075] Each R 1 and each R 2 Independently represent C1- to C 20 -alkyl, -cycloalkyl, -alkylaryl or -[AO] n -R 4 ,

[0076] Where A = C2- to C4-alkylene, R 4 Indicates H, C1- to C 20 -alkyl, -cyclohexyl or -alkylaryl,

[0077] and n = 2-350,

[0078] Each R 3 Independent of other representations NH2, -NR 5 R 6 , -OR 7 NR 8 R 9 ,

[0079] Where R 5 and R 6 Independently express

[0080] C1- to C 20 -alkyl, -cycloalkyl

[0081] -alkylaryl or -aryl,

[0082] or represents a hydroxyalkyl- or acetoxyethyl-(CH3-CO-O-CH2-CH2-) or a hydroxyisopropyl-(HO-CH(CH3)-CH2-) or an acetoxyisopropyl (CH3-CO-O-CH(CH3)-CH2-);

[0083] or R 5 and R 6 together to form a ring of which the nitrogen is a part, thereby forming a morpholine or imidazoline ring,

[0084] R 7 is a C2-C4-alkylene group,

[0085] Each R 8 and R 9 Independently represent C1- to C 20 -alkyl, -cycloalkyl, -alkylaryl, -aryl or hydroxyalkyl,

[0086] and wherein a, b, c and d represent the molar fractions of the structural units S1, S2, S3 and S4, and

[0087] a / b / c / d / =(0.1–0.9) / (0.05–0.9) / (0–0.8) / (0.0–0.8), especially a / b / c / d=(0.3–0.9) / (0.05–0.7) / (0–0.3) / (0.0–0.4)

[0088] And the premise is a+b+c+d=1.

[0089] PCE type copolymers with n=8-250, more preferably n=11-200, even more preferably n=20-150, most preferably n=30-125, in particular n=50-115 appear to be particularly advantageous for use in dry mortars.

[0090] Advantageously, the molar fractions of the structural units S1, S2, S3 and S4 are selected as follows: a / b / c / d=(0.3-0.9) / (0.05-0.9) / (0-0.3) / (0-0.4), preferably a / b / c / d=(0.3-0.9) / (0.05-0.7) / 0 / 0.

[0091] According to a particularly advantageous embodiment, the a / b ratio is between 0.5 / 1 and 15 / 1, preferably between 1 / 1 and 11 / 1, more preferably between 1.5 / 1 and 9 / 1, most preferably between 3 / 1 and 8 / 1, in particular between 6 / 1 and 7 / 1. An a / b ratio within the preferred limits leads to improved properties of the powdered copolymer P when used in a mineral binder composition and in particular in a dry mortar. Thus, a powdered copolymer P with an a / b ratio within the preferred limits results in a mineral binder or a mineral binder composition with increased initial flowability and higher compressive strength compared to powdered copolymers P with other a / b ratios.

[0092] According to a particularly advantageous embodiment, R u and R v Each represents hydrogen or methyl, m=1, p=0 and R 1 Indicates - [AO] n -R 4 , wherein A represents C2-alkylene, n=50-115, and R 4 Selected from H or CH3.

[0093] Preferred PCE-type copolymers have an average molecular weight (Mw) of 5000-150000 g / mol, in particular 10000-100000 g / mol. The average molecular weight is measured in particular using gel permeation chromatography (GPC) with polyethylene glycol (PEG) as standard.

[0094] In particular, the structural units S1, S2, S3 and S4 together have a combined molecular weight which amounts to at least 50 wt %, preferably at least 90 wt %, in particular at least 95 wt %, each based on the total dry weight of the PCE-type copolymer.

[0095] Methods for producing such PCE type copolymers are known in the art. Two main methods are used industrially to synthesize such PCE type copolymers. The first method is the free radical polymerization of ethylenically unsaturated monomers. The side chains of the formed PCE type copolymers have been attached to the monomer units. PCE type copolymers with the desired structure and properties are obtained by specific monomer selection and ratio, especially the amount of acrylic acid and methacrylic acid monomers in the polymerization reaction solution. Such free radical polymerization and the formed PCE type copolymers are described in, for example, WO2012 / 084954.

[0096] In a preferred embodiment of the invention, the PCE type copolymers are those obtained by free radical polymerization. Typical free radical polymerizations are preferably regulated with sodium hypophosphite as regulator. In a particularly preferred embodiment, the free radical polymerization is carried out at room temperature.

[0097] In the second method, called polymer-like conversion reaction, the polycarboxylic acid backbone is synthesized in a first step. Subsequently, side chains are attached to the polycarboxylic acid backbone, for example by esterification, amidation or etherification reaction with alcohols, amines, etc. Such polymer-like conversion reactions and the resulting PCE-type copolymers are described, for example, in EP1138697 and WO2005 / 090416.

[0098] It is possible that additional monomers are contained in the PCE type copolymers of the present invention. Examples of such additional monomers are styrene, α-methylstyrene, vinyl acetate, isobutylene, diisobutylene, cyclopentadiene, ethylene, propylene, N-vinylpyrrolidone, acrylamide, methacrylamide, methyl vinyl ether, ethyl vinyl ether, allylsulfonic acid, acrylamidomethacrylsulfonic acid, styrenesulfonic acid, butadiene and acrylonitrile. The sum of the molecular weights of any additional monomers contained in the PCE type copolymers of the present invention is less than 50 w%, preferably less than 10 w%, in particular less than 5 w%, each based on the total dry weight of the PCE type copolymer.

[0099] The powdered copolymer P of the invention is characterized by having a particle size distribution with a D90 value of <250 μm, preferably <225 μm, in particular <210 μm, a D10 value of <60 μm, preferably <50 μm, in particular <40 μm, and a D50 value of 70-130 μm, preferably 75-120 μm, in particular 80-100 μm.

[0100] The powdered copolymer P of the present invention can be obtained by spray-drying an aqueous solution of the above-mentioned PCE type copolymer.

[0101] There is no particular limitation on the concentration of the PCE type copolymer in the aqueous solution before spray drying. However, preferably, an aqueous solution having a PCE type copolymer concentration of at least 20 w%, more preferably at least 40 w% and up to 75 w%, each based on the total weight of the aqueous solution, can be used.

[0102] The pH of the aqueous PCE-type copolymer solution is adjusted before spray drying to >7, preferably >9, in particular >10. Such a pH of the aqueous PCE-type copolymer solution for spray drying leads to a finer particle size of the powdered copolymer P of the invention and a powder with less tendency to agglomerate.

[0103] A pH of an aqueous solution of a PCE type copolymer < 7 leads to increased sticking and agglomeration during spray drying. According to an embodiment, the pH of the aqueous solution of a PCE type copolymer is adjusted according to the number n of repeating units -[AO]-. As the number n increases, the pH needs to be increased to prevent sticking and agglomeration during spray drying. According to a particularly preferred embodiment, the number n is 50-115 and the pH is adjusted to at least 10.

[0104] According to an embodiment, the pH is adjusted by adding an oxide or hydroxide of an alkali metal, an alkaline earth metal or a mixture thereof. Preferably, the pH of the aqueous solution of the PCE type copolymer is adjusted by adding NaOH, KOH, MgO, Mg(OH)2, CaO or Ca(OH)2, most preferably Ca(OH)2.

[0105] Spray drying is a known method for producing dry powders from liquids by combining spraying with a quick drying solution. Drying can be carried out with hot gases, preferably hot air or hot nitrogen. The hot gas can be blown out in the same direction as the liquid being sprayed. It is also possible to blow the hot gas in the opposite direction to the liquid being sprayed. The liquid is dispersed with a nozzle or an atomizer, the inlet preferably being in the upper part of a spray tower. The dried powder can be separated from the hot gas by a cyclone separator.

[0106] The aqueous solution of the PCE type copolymer is preferably preheated before entering the spray dryer. If no gas is used for drying, the PCE type copolymer solution can be introduced into a spray dryer at a pressure between 0.2-40 MPa. If gas is used for drying, the PCE type copolymer solution can be introduced into a spray dryer at ambient pressure. Preferably, the drying is carried out with hot air or hot nitrogen, and the gas is preferably blown out in the same direction as the sprayed liquid. Spray drying can be carried out at an inlet temperature of 90-300°C, preferably 100-200°C, more preferably 110-150°C, and in particular 110-120°C. Lower inlet temperatures have the advantages of lower energy consumption and a lower tendency for PCE type copolymers to degrade. The outlet temperature can be 55-200°C, preferably 60-150°C, and more preferably 65-100°C.

[0107] The aqueous solution of the PCE type copolymer can enter the spray dryer by any means known to those skilled in the art, such as a nozzle, an atomizer or a centrifuge. Any spray dryer known to those skilled in the art is suitable for producing the powdered copolymer P of the present invention. The size of the spray dryer can be selected according to the target throughput.

[0108] According to a preferred embodiment, the powdered copolymer P comprises further additives. Preferred additives are anti-caking agents and antioxidants, which stabilize the powder against thermo-oxidative degradation and autoignition.

[0109] Suitable anti-caking agents can be any anti-caking agent known to those skilled in the art. Examples of anti-caking agents include powdered cellulose, magnesium stearate, calcium carbonate, dolomite, clay, kaolin, vermiculite, bentonite, talc, slag, fly ash, silicates or aluminosilicates, and silicon dioxide, such as fumed silica, precipitated silica, silica gel or silica sol.

[0110] Suitable antioxidants may be any antioxidant known to those skilled in the art. Examples of antioxidants are disclosed, for example, in WO 00 / 17263 and include alkylated monophenols, alkylated hydroquinones, alkylidene bisphenols, hydroxylated benzyl compounds, phenol-thiodiphenyl ethers, acylaminophenols, phenol esters and phenol amides.

[0111] According to an embodiment, any such other additives are added prior to the spray drying process, as this will result in improved performance of such additives. The additives may be added to the aqueous solution of the PCE type copolymer prior to spray drying. It is also possible to add one or more additives during the spray drying process, for example via a separate feed nozzle.

[0112] According to an embodiment, the content of any such other additives in the powdered copolymer P is less than 5w%, preferably less than 2w%, more preferably less than 1.5w%, in particular less than 1w%, each based on the total weight of the aqueous solution.

[0113] The resulting powder product may be sieved to remove small amounts of agglomerates which may potentially have formed.

[0114] The spray drying process can be carried out continuously or batchwise.

[0115] In a preferred embodiment of the present invention, the solid copolymer P is a powder. The powder can be converted into another solid form, for example by pressing. The copolymer P of the present invention can therefore also take the form of granules, shaped blocks, tablets, etc.

[0116] The powdered copolymer P of the present invention exhibits an alkaline reaction with water. The powdered copolymer P of the present invention can be completely redispersed in water. The pH of such a redispersion in water (with a concentration of the powdered copolymer P of the present invention of 40 w%) is at least 8, preferably at least 10, in particular at least 11.

[0117] As a further aspect, the present invention relates to a mineral binder or a mineral binder composition, in particular a dry mortar, containing the powdered copolymer P of the present invention. The mineral binder is as defined above. The mineral binder composition can take the form of, for example, a dry composition or a fluid or hardened binder composition (mixed with mixing water). The mineral binder composition can also take the form of a fully cured mineral binder composition, for example a shaped body.

[0118] The mineral binder or mineral binder composition preferably comprises the powdered copolymer P of the present invention in an amount of 0.01-10w%, preferably 0.05-5w%, more preferably 0.1-2w%, in particular 0.15-0.8w%, based on the total weight of the mineral binder. Due to the improved properties of the powdered copolymer P of the present invention, the dosage of the powdered copolymer P in the mineral binder composition can be very low.

[0119] The mineral binder composition of the invention, in particular the dry mortar, may additionally contain aggregate, preferably sand. Sand is a naturally occurring granular material which contains finely dispersed rock or mineral particles. It can be obtained in different forms and sizes. Examples of suitable sands are quartz sand, limestone sand, river sand or crushed aggregate. Suitable sands are described, for example, in the standards ASTM C 778 or EN 196-1.

[0120] Preferably, at least part of the sand is quartz sand or limestone sand or a mixture thereof, quartz sand being particularly preferred, since it is chemically inert, strong, available in different sizes and the flowability of the composition can be advantageously set.

[0121] Typically, the sand is provided as particles of different fractions passing through a sieve with clear openings. Preferred is a sand of which at least 95w% is less than 5mm, more preferably less than 4mm, even more preferably less than 3.5mm. Large particles may result in unsuitable mixing.

[0122] Preferably, the particle size of at least part of the sand is at least 100 μm, more preferably at least 200 μm. Such granulometry enables an optimized particle size distribution for homogeneous mixing, good rheology of the new mortar and high strength of the hardened mortar.

[0123] Preferred sand particle sizes are 0.04-5 mm, more preferably 0.05-4 mm and even more preferably 0.05-3.6 mm.

[0124] A preferred mineral binder composition according to the invention, in particular a dry mortar, therefore comprises 10-80 w%, preferably 25-70 w%, in particular 40-65 w% of sand, based on the total dry weight of the mineral binder composition.

[0125] It may be advantageous if the mineral binder composition of the invention, in particular the dry mortar, additionally comprises other additives for mineral binder compositions, in particular cementitious binder compositions. Such additives may be, for example, plasticizers, superplasticizers, rheology modifiers, retarders, air entraining agents, deaerators, corrosion inhibitors, fibers, synthetic organic polymers, expansion-inducing additives, pigments, strength enhancers, waterproofing additives, alkali-aggregate reaction inhibitors, chromate reducers, and / or biocides.

[0126] According to an embodiment, a synthetic organic polymer different from the PCE type copolymer described above is included in the mineral binder composition of the present invention. The synthetic organic polymer can be prepared by free radical polymerization of monomers selected from the following: ethylene, propylene, butylene, isoprene, butadiene, styrene, acrylonitrile, acrylic acid, methacrylic acid, esters of acrylic acid, esters of methacrylic acid, vinyl esters, vinyl chloride. It is preferred that the synthetic organic polymer is a copolymer synthesized from two or more, preferably two different monomers. The sequence of the copolymer can be alternating, block or random. Preferred synthetic organic polymers are vinyl acetate and ethylene, vinyl acetate and ethylene and methyl methacrylate, vinyl acetate and ethylene and vinyl ester, vinyl acetate and ethylene and acrylate, vinyl chloride and ethylene and vinyl laurate, vinyl acetate and vinyl valerate (vinylveratate), acrylate and styrene, acrylate and styrene and butadiene, acrylate and acrylonitrile, styrene and butadiene, acrylic acid and styrene, methacrylic acid and styrene, styrene and acrylate, and copolymers of styrene and methacrylate.

[0127] The glass transition temperature (Tg) of the synthetic organic polymer may vary within a wide range. Suitable synthetic organic polymers may have a Tg of, for example, -50°C to +60°C, preferably -45°C to +50°C, more preferably -25°C to +35°C.

[0128] It is possible, and in some cases preferred, to use mixtures of more than one of the synthetic organic polymers mentioned in the compositions of the present invention.

[0129] According to an embodiment, the synthetic organic polymer is used in solid form, for example in the form of a redispersible polymer powder. Such a redispersible powder can be produced, for example, by spray drying a polymer dispersion, as described, for example, in patent application EP1042391. Suitable redispersible powders are available, for example, from Wacker Chemie AG under the trade name Vinnapas. The use of redispersible powders of synthetic organic polymers is preferred in the context of the present invention.

[0130] A preferred mineral binder composition according to the invention, in particular a dry mortar, therefore comprises:

[0131] a) 10-50 w% of at least one mineral binder,

[0132] b) 0.01-10w%, preferably 0.05-5w%, more preferably 0.1-2w%, in particular 0.15-0.8w% of powdered copolymer P,

[0133] c) 0-80w%, preferably 10-65w% of aggregate,

[0134] d) 0-10 w%, preferably 0.1-6 w% of other additives selected from plasticizers, superplasticizers, rheology modifiers, retarders, air entraining agents, deaerators, corrosion inhibitors, fibers, synthetic organic polymers, expansion-generating additives, pigments, strength enhancers, waterproofing additives, alkali-aggregate reaction inhibitors, chromate reducing agents, and / or biocides, and

[0135] e) optionally water,

[0136] Each is based on the total weight of the mineral binder composition.

[0137] The mixing of components a) to e) can be carried out in any given order by a mixer usually used for producing mineral binders, mortars or concretes. The mineral binder composition according to the invention, in particular the dry mortar, can be pre-batch-mixed in the factory. It is also possible that the mineral binder composition according to the invention, in particular the dry mortar, is mixed on the construction site.

[0138] It is preferred in the context of the present invention that the mineral binder composition is a dry composition, such as a dry mortar composition. It is therefore preferred that the mineral binder composition is substantially free of water.

[0139] It has been found that a mineral binder or a mineral binder composition containing the above powdered copolymer P has increased flowability, reduced slump loss, increased compressive strength, especially at an early age, when compared to the same mineral binder or mineral binder composition with a comparative powdered copolymer.

[0140] The powdered copolymers P described above can therefore be used in a method for increasing the flowability of a mineral binder or a mineral binder composition.

[0141] The powdered copolymer P described above can further be used in a method for maintaining the flowability of a mineral binder composition within a specified time after mixing with water, for example within 20 min, preferably within 30 min, more preferably within 45 min.

[0142] The powdered copolymers P described above can also be used in a method for reducing the water demand of a mineral binder or a mineral binder composition.

[0143] Finally, the powdered copolymers P described above can be used in a method for increasing the compressive strength of a mineral binder or a mineral binder composition, in particular 1 day and / or 3 days after mixing with water. BRIEF DESCRIPTION OF THE DRAWINGS

[0144] Figure 1 The particle size distribution of polymer powders P1 and P2 prepared according to the following working examples is shown.

[0145] The following working examples illustrate the invention. These examples are not intended to limit the scope of the invention in any way.

[0146] Working Example

[0147] Preparation of polymer solution SP1

[0148] 330 g of water, 330 g of methallyl polyethylene glycol (OH-terminated, M w =4000 g / mol), 42 g of acrylic acid, 102 g of a 16% aqueous NaOH solution, 1.5 g of a 10% aqueous Fe(II)SO4.7H2O solution and 2 g of sodium hypophosphite were added to a reaction vessel with a stirrer.

[0149] Then, 10 g of a 30% aqueous hydrogen peroxide solution and 4 g of a 5% aqueous Rongalite solution were added dropwise at a temperature of 20° C. to 35° C. over a period of 70 min with stirring.

[0150] 120 minutes after the start of the dropwise addition, a clear viscous polymer solution was obtained.

[0151] Preparation of polymer solution SP2

[0152] Polymer SP2 was prepared as above for polymer SP1, but using 366 g of methallyl polyethylene glycol (OH-terminated, M w =2400 g / mol).

[0153] Preparation of polymer solution SP3

[0154] 145 g of 50 w% partially neutralized polyacrylic acid (M w =4000 g / mol) and 7.5 g of 50 w% sulfuric acid were placed in a glass reactor equipped with a thermometer, a stirrer, a gas inlet tube and a distillation assembly. The solution was heated to 70°C and 52 g of methoxy-terminated polyethylene glycol (M w=1000 g / mol) and 300 g of methoxy-terminated polyethylene glycol (M w =3000 g / mol). The mixture was heated and maintained at 165° C. under a steady stream of nitrogen. After stirring at this temperature for 6 h, the mixture was allowed to cool to room temperature. The pH of the resulting mixture was about 3.

[0155] Preparation of polymer solution SP4

[0156] Polymer SP4 was prepared as above for Polymer SP3, but using 347.5 g of methoxy-terminated polyethylene glycol (M w =5000 g / mol) instead of a mixture of two different methoxy-terminated polyethylene glycols. The pH of the resulting mixture was about 3.

[0157] Preparation of polymer powder P1

[0158] 3g of Ca(OH)2, 68g of water and 3g of fumed silica ( From Evonik) was added to 200 g of SP1. The pH of the suspension formed was about 13. The suspension formed was dried in a laboratory spray dryer of model Mini SprayDryer B-290 (Büchi AG, Switzerland). Spray drying was carried out by inserting a nozzle into the suspension at the head of the spray dryer. Compressed air with a flow rate of 600 L / h and a pressure of 0.5 MPa was used, and its flow direction was the same as that of the sprayed material. The inlet temperature was 120°C. The feed rate was adjusted so that the outlet temperature reached 65-70°C. The discharged powder was separated from the air flow by a cyclone separator.

[0159] Preparation of polymer powder P2

[0160] Polymer powder P2 was prepared as polymer powder P1 above, but the amount of Ca(OH)2 was adjusted to 60 mg. The pH of the resulting suspension was about 9.

[0161] Preparation of polymer powder P3

[0162] Polymer powder P3 was prepared as polymer powder P1 above, but without the addition of Ca(OH)2. The pH of the resulting suspension was about 5.

[0163] Preparation of polymer powder P4

[0164] Polymer powder P4 was prepared as polymer powder P1 above, but using SP2 instead of SP1.

[0165] Preparation of polymer powder P5

[0166] The polymer solution SP3 was poured into an open aluminum pan of approximately 100 mm diameter and 7 mm high and dried at ambient temperature and pressure. The solid material formed was ground into a fine powder using a standard mortar and pestle.

[0167] Preparation of polymer powder P6

[0168] Polymer powder P6 was prepared as polymer powder P5 above, but using polymer solution SP4 instead of SP3.

[0169] Table 1 below shows an overview of the powders obtained. Polymer powders P1 and P4 are according to the invention.

[0170] Table 1:

[0171]

[0172]

[0173] nm: Not measured

[0174] From Table 1 above it can be seen that spray drying from polymer solution SP1 is possible only when the pH is 9 or higher. If the pH of the polymer solution is only 5, no powder can be obtained. It can further be seen that if the pH of the polymer solution is increased to 13, a finer powder P with non-caking properties can be obtained.

[0175] Performance Tests in Cementitious Compositions (Examples M1-M6)

[0176] As a measure of the fluidity of the cementitious mixture, the slump flow test was carried out according to JC / T 985-2005 (for Examples M1-M3) and according to GB / T 50448-2008 (for Examples M4-M6). The slump flow test was measured on each sample at specified time points after mixing with the mixing water.

[0177] The compressive strength was measured according to standard GB / T 17671-1999 using a 4x4x16 cm prism at 23°C / 50% relative humidity after curing for a certain period of time, as shown in Table 2-4 below.

[0178] The linear shrinkage is measured according to JC / T 985-2005 after curing for 28 days at 23°C / 50% relative humidity.

[0179] To prepare Examples M1-M3, 200 g of cement (CEM I52.5), 340 g of calcium aluminate cement, 160 g of α-hemihydrate, 400 g of limestone, 860 g of quartz sand (0.1-0.3 mm particles) and 4 g of each of powders P1, P4 and P6 were dry mixed in a Hobart mixer at 23° C. for 1 minute to obtain a dry mortar.

[0180] Within 10 seconds, mixing water was added to the dry mix to give a water / binder ratio of 0.22. Mixing was continued for 170 seconds.

[0181] Table 2 below shows an overview of the results.

[0182] Table 2:

[0183]

[0184]

[0185] These results show that the powders P1 and P4 according to the invention have good liquefaction properties and particularly low slump flow losses over time. The powders according to the invention also lead to increased compressive strength after 1 day and low shrinkage.

[0186] To prepare Examples M4-M6, 750 g of cement (CEM I52.5), 120 g of blast furnace slag, 40 g of fumed silica, 340 g of fine quartz sand, 120 g of fine river sand (particle size 0.3-0.6 mm), 560 g of coarse river sand (particle size 0.6-2.3 mm) and 2.8 g of each of powders P1, P4 and P5 were dry mixed in a Hobart mixer at 23° C. for 1 minute to obtain a dry mortar.

[0187] Within 10 seconds, mixing water was added to the dry mix to give a water / binder ratio of 0.15. Mixing was continued for 170 seconds.

[0188] Table 3 below shows an overview of the results.

[0189] Table 3:

[0190]

[0191] These results show that the powders P1 and P4 according to the invention have good liquefaction properties and particularly low slump flow losses over time. The powders according to the invention also lead to an increase in the compressive strength after 3 days.

Claims

1. A method for producing a powdered copolymer P, the method comprising the following steps: i) preparing a copolymer aqueous solution comprising 30-99 weight percent, each based on the total weight of the aqueous solution, of a PCE type copolymer, wherein the PCE type copolymer comprises: a) a molar parts of structural unit S1 of formula I b) b molar parts of structural unit S2 of formula II c) c molar parts of structural unit S3 of formula III d) d molar parts of structural unit S4 of formula IV in Each M represents H independently of each other + , alkali metal ions, divalent or trivalent metal ions, ammonium ions or organic ammonium groups, Each R u independently of one another represent hydrogen or methyl, Each R v independently of each other represent hydrogen or COOM, m=0, 1, 2 or 3, p = 0 or 1, Each R 1 and each R 2 Independently represent C1- to C 20 -alkyl, -cycloalkyl, -alkylaryl or -[AO] n -R 4 , Where A = C2- to C4-alkylene, R 4 Indicates H, C1- to C 20 -alkyl, -cyclohexyl or -alkylaryl, and n=2-350, Each R 3 Independent of other representations NH2, -NR 5 R 6 、-OR 7 NR 8 R 9 , Where R 5 and R 6 Independently express C1- to C 20 -alkyl, -cycloalkyl, -alkylaryl or -aryl, or hydroxyalkyl or acetoxyethyl or hydroxyisopropyl or acetoxyisopropyl; or R 5 and R 6 together to form a ring of which the nitrogen is a part, thereby forming a morpholine or imidazoline ring, R 7 is a C2-C4-alkylene group, Each R 8 and R 9 Independently represent C1- to C 20 -alkyl, -cycloalkyl, -alkylaryl, -aryl or hydroxyalkyl, and wherein a, b, c and d represent the molar fractions of the structural units S1, S2, S3 and S4, and a / b / c / d / =(0.1–0.9) / (0.1–0.9) / (0–0.8) / (0–0.8), And the premise is that a+b+c+d=1, ii) adding alkali to adjust the pH of the solution to >10, iii) adding 0.01-5w% of at least one additive selected from anti-caking agents and / or antioxidants, each based on the weight of the polymer solution, iv) spray drying the aqueous solution to obtain a powder, and v) optionally sieving; The particle size distribution of the powdered copolymer P is: D90<250 μm, D10<60 μm, and D50 is 70-130 μm.

2. The method according to claim 1, wherein the aqueous copolymer solution comprises 40-95 w% of the PCE type copolymer.

3. The method according to claim 1, wherein the aqueous copolymer solution comprises 50-90 w% of the PCE type copolymer.

4. The method according to claim 1, wherein each M independently represents an alkaline earth metal ion.

5. The method according to claim 1, wherein 0.05-2 w% of at least one additive selected from anti-caking agents and / or antioxidants is added.

6. The method according to claim 1, wherein 0.1-1 w% of at least one additive selected from anti-caking agents and / or antioxidants is added.

7. The method according to claim 1, wherein the D90 <225 μm.

8. The method according to claim 1, wherein the D90 <210 μm.

9. The method according to claim 1, wherein the D10 <50 μm.

10. The method according to claim 1, wherein the D10 <40 μm.

11. The method according to claim 1, wherein the D50 is 75-120 μm.

12. The method according to claim 1, wherein the D50 is 80-100 μm.

13. The method according to claim 1, wherein each R in the powdered copolymer P 1 and R 2 Independently of each other - [AO] n -R 4 , where each R 4 are independently selected from H or CH3, and wherein n is 50-115.

14. The method according to claim 1, wherein the ratio a / b in the powdered copolymer P is 1.5 / 1 to 9 / 1.

15. The method according to claim 1, wherein the ratio a / b in the powdered copolymer P is 3 / 1 to 8 / 1.

16. The method according to claim 1, wherein the ratio a / b in the powdered copolymer P is 6 / 1 to 7 / 1.

17. The process according to claim 1, characterized in that the copolymer in step i) is prepared by a free radical polymerization process.

18. The process according to claim 1, characterized in that the base added in step ii) is selected from LiOH, NaOH, KOH, Mg(OH)2, Ca(OH)2 or mixtures thereof.

19. The process according to claim 18, characterized in that the base added in step ii) is Ca(OH)2 and the pH is 10-14.

20. The process according to claim 1, characterized in that step iv) is carried out at a spray drying inlet temperature of not more than 150°C.

21. The process according to claim 1, characterized in that step iv) is carried out at a spray drying inlet temperature of not more than 120°C.

22. Use of the powdered copolymer P prepared by the process according to any one of claims 1 to 21 in a mineral binder composition.

23. Use according to claim 22, characterised in that the mineral binder composition is a dry mortar.

24. Use of a powdered copolymer P prepared according to the process according to any one of claims 1 to 21 for reducing the water demand of a mineral binder composition.

25. Use of a powdered copolymer P prepared according to any one of claims 1 to 21 for increasing the flowability of a mineral binder composition.

26. Use of a powdered copolymer P prepared according to the process according to any one of claims 1 to 21 for improving the slump life of a mineral binder composition.

27. Use of a powdered copolymer P prepared according to the process according to any one of claims 1 to 21 for increasing the compressive strength of a mineral binder composition.

28. A mineral binder composition comprising: a) 10-50w% of at least one mineral binder, b) 0.01-10w% of a powdered copolymer P prepared by the method according to any one of claims 1-21, c) 0-80w% aggregate, d) 0-10w% of other additives selected from the group consisting of plasticizers, superplasticizers, rheology modifiers, retarders, air entraining agents, deaerators, corrosion inhibitors, expansion generating additives, pigments, strength enhancers, waterproofing additives, alkali-aggregate reaction inhibitors, chromate reducing agents and / or biocides, Each is based on the total weight of the mineral binder composition.

29. The mineral binder composition according to claim 28, which is a dry mortar.

30. The mineral binder composition according to claim 28, comprising 0.05-5 w% of a powdered copolymer P prepared according to the process according to any one of claims 1-21.

31. The mineral binder composition according to claim 28, comprising 0.1 to 2 w% of a powdered copolymer P prepared according to a process according to any one of claims 1 to 21.

32. The mineral binder composition according to claim 28, comprising 0.15-0.8 w% of a powdered copolymer P prepared according to the process according to any one of claims 1 to 21.

33. A mineral binder composition according to claim 28, comprising 10-65 w% aggregate.

34. The mineral binder composition according to claim 28, comprising 0.1-6 w% of said other additives.

35. The mineral binder composition according to claim 28, which additionally contains water.

36. A shaped body obtained by curing a mineral binder composition according to any one of claims 28 to 35.

Citation Information

Patent Citations

  • Redispersible polymer powders

    EP1042391A1

  • Polymers for cement dispersing admixtures

    EP1138697A1

  • Powder dispersant for hydraulic compositions

    US7030178B2

  • Stabilized water-soluble polymer powders on the basis of polyoxy alkylene glycol carboxylates and method for producing same

    WO2000017263A1

  • Powdery polyethercarboxylate-based polymeric compositions

    WO2000047533A1